A Critical Analysis of the Book Verb Valency and Basic Constructions of Sentences in Modern Persian; a Survey based on Dependency Grammar Theory - Sepideh Abdolkarimi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The present article is the result of a critical look at the book “Verb Valency and Basic Constructions of Sentences in Modern Persian; a Survey based on Dependency Grammar Theory” which is written by Dr. Omid Tabibzadeh in eight chapters. Due to the fact that the dependency approach to grammar in Iran has gained less attention than other grammatical approaches, the lack of the presence of such a book in Persian, introducing this grammatical approach to language researchers interested in this approach, was strongly felt. For this reason, author’s attempt is admirable. One of the challenges the author has faced has been equivalent choices for technical terms in the named approach, and the absence of books in this field in Persian has resulted in the present situation which is the lack of Persian sources in Dependency Grammar. Because of the mentioned lack, sometimes we face a variety of technical terms, ambiguous definitions, and counterexamples in traditional grammars. Therefore, this article is the introduction of the book, its chapters, its strong points, and also its weak points.